Examining the “gang penalty” in the juvenile justice system: a focal concerns perspective - Walker, D’Andre (Youth violence and juvenile justice, 2020)
There are hundreds of thousands of juvenile gang members in the United States who are at heightened risk of criminal offending, violent victimization, and incarceration. Importantly, however, incarceration in itself is a lifelong risk factor for negative social outcomes. That said, little is known about the effects of gang membership on the sentencing outcomes of juvenile offenders. The primary research question of the current study is: How does self-reported gang membership influence the likelihood of incarceration relative to similarly situated non-gang-involved juvenile defendants? To address this question, the current study uses data obtained from the Pathways to Desistance study. In a sample of 1,067 serious adolescent offenders drawn from Wave I, results show that gang affiliation is a significant predictor of incarceration. This finding was consistent across the two study sites (Phoenix, AZ, and Philadelphia, PA), ultimately providing support for a “gang penalty” in juvenile sentencing outcomes. The implications for future research, juvenile justice policy, and youth development are discussed.